E-DAKWAH DALAM PESANTREN VIRTUAL - Akhmad Rifa’i (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
The research aims to recognize, inform and to simplify the management of dakwah in the cyber or virtual media. The result of the study may support and provide inspiration of Muslim society to develop and create an innovative dakwah in virtual media. The primary data are obtained from the Virtual Pesantren. The data concern with the management of the Virtual Pesantren concerning its service on religious information that is interesting and that contains educational programs. To analyze the data, the study uses qualitative-descriptive technique and the commentary of the data is in the form of narrative reports. The finding shows that the creativity of Islamic students or management in carrying out the Virtual Pesantren is very innovative and high performance. Infact, many users who visit or attend as members o f the Virtual Pesantren prove these findings. Moreover, the virtual Pesantren becomes a service agent on religious information that is open for all societies and religions.